A Study of Some Erythrocyte Indices and Bacteriological Analysis of Broiler-chickens Raised on Maggot-meal Based Diets - Awoniyi, T.A.M.; Adebayo, I.A.; Aletor, V.A. (International Journal of Poultry Science, 2004)
Five treatment groups of 18 broiler-chickens each from age 4-9 weeks were fed diets in which maggot meal (MGM) replaced 0, 25, 50, 75 and 100% of fish meal (FM) on equi-protein basis. Ethyledine Di Tetra Acetic acid (EDTA)-treated blood samples were taken from each of the groups and subjected to total erythrocyte counts, packed cell volume (PCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and mean corpuscular volume (MCV). Results therefrom showed no significant (p > 0.05) difference and also compared favourably with the normal physiological values for these indices in healthy chickens. Isolation and characterization of bacterial organisms in the different broiler-chicken diets formulated with varying levels of maggot meal obtained from fresh droppings of the experimental chickens and some visceral organs in addition to development medium of the maggot were carried out. Findings revealed that most bacteria associated with the broiler-chickens fed maggot meal-based diets in this study are by far those that are commonly experienced by man and animals in their day to day exposure and to which their bodies have developed some relative immunity. It was concluded that since MGM inclusion in the diets of broiler-chickens does not negatively influence the erythrocyte indices and that the bacterial flora isolated from the different parts of the experimental chickens were similar to those found in fish meal fed diets, MGM could effectively replace the more expensive FM without threatening the blood physiology of the chickens and health of consumers of such broiler-chickens.